On the Limit from q-Racah Polynomials to Big q-Jacobi Polynomials - Koornwinder, T.H. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
A limit formula from q-Racah polynomials to big q-Jacobi polynomials is given which can be considered as a limit formula for orthogonal polynomials. This is extended to a multi-parameter limit with 3 parameters, also involving (q-)Hahn polynomials, little q-Jacobi polynomials and Jacobi polynomials. Also the limits from Askey-Wilson to Wilson polynomials and from q-Racah to Racah polynomials are given in a more conceptual way.